HUBUNGAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MEKANIKA TEKNIK II PADA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI JAKARTA - Dedi Hariyanto; R Eka Murtinugraha; Tuti Iriani (Jurnal Pensil)
The aim of this research knows the relationship between self-learning and learning output of the Mechanics of Structure II subject for the students of Building Engineering Education Program Department of Civil Engineering State University of Jakarta in June 2011 which involved 50 students as the sample of this research.